ANALISIS PERHITUNGAN PAJAK RESTORAN SESUAI UU NO. 28 TAHUN 2009 DENGAN PAJAK PENGHASILAN PASAL 21 UNTUK MENENTUKAN LABA BERSIH SETELAH PAJAK (STUDI KASUS PADA DESATU COFFEE KOTA KEDIRI) - Rafi Kusuma Dewi; Khasanah Sahara; Ninik Anggraini; Srikalimah (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to explain the calculation of Restaurant Tax according to Law no. 28 of 2009 with income tax article 21 to determine net profit after tax at Desatu Coffee, Kediri City. This research uses quantitative descriptive methods. The data source in this research is primary data. Data collection techniques were carried out by means of interviews and documentation. The analysis technique used in the research is qualitative descriptive analysis. In this research, the results showed that Desatu Coffee had calculated restaurant tax in accordance with the restaurant tax rate set by the Regional Government of Kediri City, namely 10% of the price of food and drinks as the basis for tax imposition. However, Desatu Coffee does not calculate and pay income tax article 21 which results in differences in tax calculations which can affect the net profit after tax obtained by Desatu Coffee. The effect of paying income tax on profits is that the profit that will be obtained will be lower, but if you pay income tax it will be better because you will not commit a tax violation and will be free from administrative sanctions in the form of fines, interest or increases as well as free from criminal sanctions in the form of fines. criminal, imprisonment or imprisonment.